Methicillin-resistant Staphylococcus aureus in Papua New Guinea: A community nasal colonization prevalence study - Laman, M.; Greenhill, A.; Coombs, Geoffrey; Robinson, James; Pearson, J.; Davis, T.; Manning, L. (Elsevier Ltd, 2017)
Background: There are few epidemiological data available to inform a national response to communityacquired methicillin-resistant Staphylococcus aureus (MRSA) in Papua New Guinea (PNG). Methods: We performed a cross-sectional survey to determine the pattern of MRSA nasal colonization and the diversity of circulating MRSA clones among adults and adolescents in Madang Province, PNG. Results: S. aureus nasal colonization was confirmed in 44 (17.1%) of 257 participants. Four (9.1%) isolates were methicillin resistant. Resistance to other antimicrobial agents was uncommon. Detailed molecular typing of three MRSA isolates demonstrated multiple MRSA clones in this community, of which two carried the Panton-Valentin leukocidin-associated virulence genes. Conclusions: MRSA is likely to account for a clinically important proportion of staphylococcal disease in PNG. There are multiple MRSA clones in PNG. Ongoing surveillance of community and invasive isolates is a critical component of an effective response to the challenge of community-acquired MRSA in this and many other resource-limited contexts.